16-6(-3x+4)=-2

Simple and best practice solution for 16-6(-3x+4)=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 16-6(-3x+4)=-2 equation:


Simplifying
16 + -6(-3x + 4) = -2

Reorder the terms:
16 + -6(4 + -3x) = -2
16 + (4 * -6 + -3x * -6) = -2
16 + (-24 + 18x) = -2

Combine like terms: 16 + -24 = -8
-8 + 18x = -2

Solving
-8 + 18x = -2

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8' to each side of the equation.
-8 + 8 + 18x = -2 + 8

Combine like terms: -8 + 8 = 0
0 + 18x = -2 + 8
18x = -2 + 8

Combine like terms: -2 + 8 = 6
18x = 6

Divide each side by '18'.
x = 0.3333333333

Simplifying
x = 0.3333333333

See similar equations:

| 2x-9=6x+4 | | c/5-4=3 | | 38+x=2x+6x-2 | | 8*w=52 | | 16-6(-3x+4)=2 | | 31-4x=5x+19 | | 22=8x+1-5X | | x^2+17x+31=4x-5 | | 24+-2a+3=7a | | 5(3-x)=-(1+x) | | x^2+x-18=2 | | -24=-4(k+3) | | 7h-7=17+4h | | y=x^2-7x+6 | | -2x+4=3(x-7) | | 21+9y-10=-277 | | 7x+9=8x+4 | | -7(x+9)=8x+42 | | 3(b+2)+2(x-5)=2 | | (2-z)(5z+3)=0 | | 5m+3=6m+7 | | 3(x+8)-8x=29 | | 3x^2=-6x-2 | | 9p+8q=100 | | 36x-4x+9+25x+7= | | (3x^2-6)=0 | | -(6(5xy+y^3)+5(9xy+7y^3))= | | -2a-11=7+7a | | 5x+5=-21-7x | | -3x^2-4x-5=0 | | 12p+6q=114 | | 2x*2x*2x+3x*3x*3x= |

Equations solver categories